New phase and deformation behavior in directional solidified NiTiAl based intermetallic alloy upon cyclic tensile loading-unloading. (15th November 2016) - Zheng, L.J.; Zhang, F.X.; Ding, R.G.; Wang, F.F.; Zhang, H.
Abstract: In the present paper, to understand the nature of newly designed Ni43Ti4Al2Nb2Hf alloys in the case of avoiding shape memory, TEM and HREM were used to reveal the precipitation type, phase composition and its relationship with the hardness. Cyclic tensile loading-unloading test is also carried out to study the deformation behavior. It is observed that a new phase with the approximate composition of Ti36 ± 2 -Ni34 ± 2 -Nb20 ± 2 -Al8 ± 1 -Hf2 ± 0.5 precipitates in the directional solidified Ni43Ti4Al2Nb2Hf alloy, which is identified to be the base-centred monoclinic lattice with lattice parameters a = 0.987 nm, b = 0.504 nm, c = 1.172 nm, α = γ = 90°, β = 130.18°, and space group C2/c. The hardness of the Ni36Ti20Nb8Al2Hf alloy with same composition to the new phase is more than 810 HV, nearly twice of that of the Ni43Ti4Al2Nb2Hf alloy, which confirms the strengthening effect of the new phase. In addition, the cyclic loading results indicate that the linear recoverable strain is more than 3%, which exhibits the significantly enhanced load capability of this alloy. Graphical abstract: Highlights: A new phase was discovered in directional solidified Ni43Ti4Al2Nb2Hf(at%) alloy. The crystal structure of the new phase was determined by TEM. The new phase dramatically increases the strength of the directional solidified NiTiAl-based alloy. The directional solidified Ni43Ti4Al2Nb2Hf alloy exhibits remarkably recoverable, superelastic strain (above 3%) deformation behavior.